The Impact of Homeostatic and Circadian Sleep Processes on Non-Suicidal Self-Injury and Suicide Urges in Borderline Personality Disorder. Issue 3 (3rd July 2022) - Fitzpatrick, Skye; Varma, Sonya; Ip, Jennifer
Abstract: Objective: Borderline personality disorder (BPD) involves high rates of non-suicidal self-injury (NSSI) and suicidal behaviors, which are often preceded by urges. Disrupted sleep processes have been linked to NSSI and suicidal behaviors. However, it is unclear which specific sleep processes influence NSSI and suicide urges at rest (i.e., baseline) or in response to distress (i.e., reactivity) in BPD, and thus require targeting in BPD-specific interventions. This study examined whether two distinct homeostatic sleep processes (i.e., total sleep time [TST] and time in bed [TIB]), and one circadian sleep process (i.e., chronotype, or tendencies toward early versus late bed and rise times) predict baseline NSSI and suicide urges and urge reactivity in BPD. Methods: Forty adults with BPD completed a seven-day sleep diary to measure average TST and TIB. They then completed a questionnaire to measure chronotype and underwent an experiment wherein they rated NSSI and suicide urges at baseline and following an emotion induction. Results: Generalized estimating equations revealed that higher TST was associated with lower baseline NSSI urges, and lower suicide urge reactivity. Additionally, higher TIB predicted higher NSSI urge reactivity. Conclusions: Sleep deprivation and extended time in bed may increase proclivity toward NSSI and/or suicide. Targeting these variables in BPD interventions may ultimately facilitate the reduction of NSSI and suicidal acts. Highlights: Higher total sleep time predicts lower baseline NSSI urges, suicide urge reactivity Higher time in bed predicts higher NSSI urge reactivity Reducing sleep deprivation in BPD may facilitate reductions in suicide, NSSI urges